VanI: a novel d‐Ala‐d‐Lac vancomycin resistance gene cluster found in Desulfitobacterium hafniense. Issue 5 (5th July 2014) - Kruse, Thomas; Levisson, Mark; de Vos, Willem M.; Smidt, Hauke
Summary The glycopeptide vancomycin was until recently considered a drug of last resort against Gram‐positive bacteria. Increasing numbers of bacteria, however, are found to carry genes that confer resistance to this antibiotic. So far, 10 different vancomycin resistance clusters have been described. A chromosomal vancomycin resistance gene cluster was previously described for the anaerobic Desulfitobacterium hafniense Y51. We demonstrate that this gene cluster, characterized by its d‐Ala‐d‐Lac ligase‐encoding vanI gene, is present in all strains of D. hafniense, D. chlororespirans and some strains of Desulfosporosinus spp. This gene cluster was not found in vancomycin‐sensitive Desulfitobacterium or Desulfosporosinus spp., and we show that this antibiotic resistance can be exploited as an intrinsic selection marker for Desulfitobacterium hafniense and D. chlororespirans. The gene cluster containing vanI is phylogenetically only distantly related with those described from soil and gut bacteria, but clusters instead with vancomycin resistance genes found within the phylum Actinobacteria that include several vancomycin‐producing bacteria. It lacks a vanH homologue, encoding a D‐lactate dehydrogenase, previously thought to always be present within vancomycin resistance gene clusters. The location of vanH outside the resistance gene cluster likely hinders horizontal gene transfer. Hence, the vancomycin resistance cluster in D. hafniense should be regarded a novel one that we here designated vanI after its unique d‐Ala‐d‐Lac ligase.